Comparison of clinical outcome between stereotactic body radiotherapy and radiofrequency ablation for unresectable hepatocellular carcinoma. Issue 4 (28th January 2022) - Ji, Ren; Ng, Kelvin K.; Chen, Wenqi; Yang, Weihong; Zhu, Hongtao; Cheung, Tan-To; Chiang, Chi-Leung; Wong, Tiffany C.L.; Kong, Feng-Ming; Wu, G.; Lo, Chung-Mau
Abstract : Abstract: Stereotactic body radiotherapy (SBRT) is a novel noninvasive treatment for unresectable hepatocellular carcinoma (HCC). Whether its efficacy is comparable to radiofrequency ablation (RFA), a recommended therapy for unresectable HCC, is unknown. The present study aims to compare the clinical outcome between SBRT and RFA for patients with unresectable HCC. The clinical data of 60 patients with unresectable HCC from January 2018 to January 2021 were retrospectively reviewed. There were 22 cases treated by SBRT and 38 cases by RFA. The short-term and long-term clinical outcomes were compared. There was no significant difference in the baseline demographic characteristics between two groups. The complete remission rate at 3 months was comparable between SBRT group (81.8%) and RFA group (89.4%). Local tumor control rate was also similar between two groups (90.9% vs. 94.7%). There was no severe complication (grade IIIa or above) in both groups. The 1-year and 2-year overall survival rates were 88.2% and 85.7% in SBRT group and 100% and 75% in RFA group, respectively. There was no statistical significant difference between groups ( P = .576). SBRT can achieve similar short and long-term clinical outcome as RFA for unresectable HCC. Future prospective clinical study is needed to justify its role in patients with HCC.